2015
DOI: 10.1007/s00223-015-0036-z
|View full text |Cite
|
Sign up to set email alerts
|

Serum Circulating MicroRNAs as Biomarkers of Osteoporotic Fracture

Abstract: Osteoporosis is a common skeletal disorder characterized by increased risk of bone fracture (BF) due to fragility. BFs, particularly hip fracture, are a major concern in health care because of the associated morbidity and mortality, mainly in the elderly. Lately the involvement of epigenetic mechanisms in the pathophysiology of many diseases has been recognized. In this context, the identification of microRNAs (miRNAs) specific to BF should represent a substantial step forward in diagnostics and therapeutics. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
106
3

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 128 publications
(112 citation statements)
references
References 26 publications
(31 reference statements)
2
106
3
Order By: Relevance
“…Recently, the diagnostic potential of circulating miRNAs for postmenopausal osteoporosis has been investigated and some miRNAs were identified as potential biomarkers10121314. Because of the diverse study designs and models, more studies were required to establish circulating miRNAs biomarkers for osteoporosis with high specificity and sensitivity.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, the diagnostic potential of circulating miRNAs for postmenopausal osteoporosis has been investigated and some miRNAs were identified as potential biomarkers10121314. Because of the diverse study designs and models, more studies were required to establish circulating miRNAs biomarkers for osteoporosis with high specificity and sensitivity.…”
Section: Discussionmentioning
confidence: 99%
“…Weilner et al showed that miR-328-3p and let-7g-5p were down-regulated in the serum of patients with osteoporotic fracture and could modulate the osteogenic differentiation of human mesenchymal stem cells in vitro 13. Meanwhile, Panach et al identified three up-regulated miRNAs (miR-122-5p, miR-125b-5p and miR-21-5p) were valuable biomarkers for osteoporotic fracture14. Due to the diverse nature of study designs, the number and type of regulated miRNAs identified varies significantly9.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…These data were validated on a further 12 fractured women vs. 11 controls, confirming miR-22-3p, miR-328-3p, and let-7g-5p as differentially expressed in the presence of a fracture. Panach et al measured a panel of 179 miRNAs in the serum samples of eight osteoporotic women with fractures vs. five controls, and validated data on 15 patients with fractures vs. 12 controls [61]. They determined that miR-122-5p, miR-125b-5p, and miR-21-5p were upregulated in the presence of a fracture.…”
Section: Mirnas In Bone Biologymentioning
confidence: 99%
“…MiR‐125b‐5p level was found to be inversely correlated with BMD at the femoral head, with an increased expression being observed in osteoblast and osteoclast from osteoporotic patients . When comparing the circulating miRNAs in patients with osteoporotic fracture with those in osteoarthritic controls, circulating miR‐125b‐5p was also significantly upregulated in the osteoporotic fracture group …”
Section: Mirnas In Human Osteoporosis Studiesmentioning
confidence: 94%